Dual dynamics: Project-based institutional work and subfield differences in the Dutch construction industry. Issue 2 (February 2019) - Lieftink, Bente; Smits, Armand; Lauche, Kristina
Abstract: This article examines how actors use relational institutional work in inter-organizational projects (IOPs) to mobilize key stakeholders from two loosely coupled subfields with the aim to institutionalize a new project delivery method with new underlying practices. In our longitudinal case study in a project-based business, in this case the Dutch construction industry, we identified three types of relational institutional work: awareness creation, selective networking, and coalition building. We found that institutional work was relatively effective in the co-supplier subfield and less effective in the architectural subfield. We explain this by zooming in on the differences between these two subfields on three interrelated dimensions that manifested themselves in institutional IOPs: nature of activities, social positions, and coopetition. Our study connects the literature on IOPs with developments in institutional theory and further advances the institutional project management literature. Highlights: Institutional change processes can consist of various IOPs that are linked. There can be differences in institutional work between IOPs in different subfields. Subfield characteristics influence institutional work in IOPs and its effectiveness.